2004
DOI: 10.3133/sir20045157
|View full text |Cite
|
Sign up to set email alerts
|

August median streamflow on ungaged streams in Eastern Coastal Maine

Abstract: Methods for estimating August median streamflow were developed for ungaged, unregulated streams in eastern coastal Maine. The methods apply to streams with drainage areas ranging in size from 0.04 to 73.2 square miles and fraction of basin 0.003 to 31.0 cubic feet per second or from 0.1 to 0.6 cubic feet per second per square mile. Estimates of August median streamflow on ungaged streams in eastern coastal Maine, within the range of acceptable explanatory variables, range from 0.003 to 45 cubic feet per second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The regional studies of small basins on ungaged streams in eastern Aroostook County, Maine, (Lombard and others, 2003) and August median streamflows on ungaged streams in eastern coastal Maine (Lombard, 2004b) have demonstrated that estimates of August median streamflow developed from statewide equations designed for basins with large drainage areas (greater than 10 mi 2 ) and small percentages of sand and gravel aquifers (less than 30 percent) are not applicable to all small basins (less than 10 mi 2 ) in Maine, especially those basins underlain by greater than 30 percent sand and gravel aquifers. The percentage of the basin underlain by sand and gravel aquifers and the drainage area were used in the equation to estimate August median streamflows for small basins in eastern coastal Maine (Lombard, 2004b). Mean basin elevation and drainage area were used in the equation to estimate August median streamflows for small basins in eastern Aroostook County, Maine (Lombard and others, 2003).…”
Section: June and August Median Streamflows Estimated For Ungaged Strmentioning
confidence: 99%
“…The regional studies of small basins on ungaged streams in eastern Aroostook County, Maine, (Lombard and others, 2003) and August median streamflows on ungaged streams in eastern coastal Maine (Lombard, 2004b) have demonstrated that estimates of August median streamflow developed from statewide equations designed for basins with large drainage areas (greater than 10 mi 2 ) and small percentages of sand and gravel aquifers (less than 30 percent) are not applicable to all small basins (less than 10 mi 2 ) in Maine, especially those basins underlain by greater than 30 percent sand and gravel aquifers. The percentage of the basin underlain by sand and gravel aquifers and the drainage area were used in the equation to estimate August median streamflows for small basins in eastern coastal Maine (Lombard, 2004b). Mean basin elevation and drainage area were used in the equation to estimate August median streamflows for small basins in eastern Aroostook County, Maine (Lombard and others, 2003).…”
Section: June and August Median Streamflows Estimated For Ungaged Strmentioning
confidence: 99%
“…Dudley (2004) derived statewide equations for estimating monthly and annual mean and median streamflows as well as the 7-day low flow with a 10 percent annual exceedance probability, superseding similar equations derived by Parker (1977). A few regional studies within Maine have produced regression equations for specific months: June and August median streamflows in southern Maine (Lombard, 2010), August median streamflows in eastern coastal Maine (Lombard, 2004), and August median streamflows in eastern Aroostook County (Lombard and others, 2003). In 2012, the USGS began a cooperative investigation with the Maine Department of Transportation (MDOT) to derive statewide regression equations that can be used to estimate monthly and annual mean and 1, 5,10,25,50,75,90,95, and 99 percentile streamflows for ungaged rivers in Maine.…”
Section: Introductionmentioning
confidence: 98%
“…Determination of low‐flow statistics through regional regression analysis typically has produced estimates with wide confidence intervals (Smakhtin ) and was often based on assumptions of stationarity (Ries and Friesz ; Flynn ; Lombard et al. ; Dudley , ; Lombard , ; Bent et al. ).…”
Section: Introductionmentioning
confidence: 99%